2018
DOI: 10.12688/f1000research.13605.1
|View full text |Cite
|
Sign up to set email alerts
|

Timely referral saves the lives of mothers and newborns: Midwifery led continuum of care in marginalized teagarden communities – A qualitative case study in Bangladesh

Abstract: Background: Prompt and efficient identification, referral of pregnancy related complications and emergencies are key factors to the reduction of maternal and newborn morbidity and mortality. As a response to this critical need, a midwifery led continuum of reproductive health care was introduced in five teagardens in the Sylhet division, Bangladesh during 2016. Within this intervention, professional midwives provided reproductive healthcare to pregnant teagarden women in the community.  This study evaluates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 13 publications
(21 reference statements)
1
30
0
Order By: Relevance
“…These factors make it hard to disentangle the contribution of each component of the intervention. A recent study in Bangladesh, also highlighted that important factors in a successful referral included early detection of complications experienced by mothers, quality support by a midwife, and quick transfer to the referral center. Our study findings were consistent with these findings and provide further evidence for the utility of an automated electronic communication system to serve as an assist in the timely referral and management of obstetric and newborn complications along with the overall positive impact of the EMAS‐related referral interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors make it hard to disentangle the contribution of each component of the intervention. A recent study in Bangladesh, also highlighted that important factors in a successful referral included early detection of complications experienced by mothers, quality support by a midwife, and quick transfer to the referral center. Our study findings were consistent with these findings and provide further evidence for the utility of an automated electronic communication system to serve as an assist in the timely referral and management of obstetric and newborn complications along with the overall positive impact of the EMAS‐related referral interventions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Bangladesh, 34 also highlighted that important factors in a successful referral included early detection of complications experienced by mothers, quality support by a midwife, and quick transfer to the referral center. Our study findings were consistent with these findings and provide further evidence for the utility of an automated elec-…”
Section: Type Of Observationmentioning
confidence: 99%
“…These challenges are not unique to Indonesia. A study conducted in Bangladesh found an absence rate of 40% for doctors in subdistrict‐level hospitals and 74% in health centers. A study in 78 CEmONC facilities across Afghanistan found that only 49% reported having at least one ob/gyn on staff while 95% had at least one medical doctor on staff.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some additional proxy indicators measure whether cases are managed better, which is assumed to improve outcomes, for example, early referral if prolonged labour or antenatal transfer to higher level of neonatal care. 108 In practice, they will need to be mapped to the local context, as the appropriate time for referral in case of, for example, prolonged labour varies depending on the location and context (availability of medication and of the facility.…”
Section: Discussionmentioning
confidence: 99%
“…108 Examples of proxy indicators are: antenatal transfer to higher level of neonatal care, early identification of danger signs predicting severe new-born illness to be assessed during postnatal contacts (predictive for need for hospitalisation).…”
Section: Availability Of Ultrasoundmentioning
confidence: 99%